Impact of gas formation kinetics on dough development and bread quality. (October 2015) - Verheyen, C.; Albrecht, A.; Elgeti, D.; Jekle, M.; Becker, T.
Abstract: The baking performance and gas retention capacity of wheat dough depends on production rate and total volume of CO2 during fermentation. This study aims to examine the effect of the CO2 formation kinetics and the gas volume fraction on the structural integrity of wheat dough and the resulting bread quality. The gas release characteristics were evaluated using a rheofermentometer with varied concentrations of compressed yeast and instant dry yeast (CY and IDY respectively). For this purpose, the maximum CO2 formation rate was calculated through the derivation of hydrostatic pressure curves measured in the rheofermentometer. For CY, the time when gas escapes the dough matrix (Tx, time of porosity) as well as the corresponding gas volume depended on the gas formation rate, whereas the gas retention capacity of wheat dough leavened with IDY was not affected by the CO2 formation rate. Although the dough leavened with IDY showed improved extensibility during fermentation, the specific bread volume was 21% below that of the samples leavened with CY. These results indicate that an increase in the maximum gas formation rate considerably affects the structural integrity of the dough matrix. Because of the reduction of the loaf volume, the effect is reinforced by the application of IDY. Highlights: Maximum CO2 formation rate is directly linked to yeast concentration and activity. A higher CO2 formation rate relates to earlier termination of gas production. CO2 formation rate does not affect gas retention capacity of dough leavened with IDY. Rheofermentometer data cannot be used exclusively to predict loaf volume. Longer fermentation with low yeast concentration impaired foam stability.